Fracture behavior of bolted joints in composites repaired with patch: 3D numerical approach - Gunduz, Yunus; Kaman, Mete Onur (Pamukkale Univ, 2018)
In this study, fracture behavior of bolted joints in composite plates containing cracks repaired with single-sided composite patch was numerically investigated. The effects of variation of parameters such as plate and patch materials, pin diameter and adhesive properties on stress intensity factor ate crack tip were investigated. In the solution, the plate repaired with the patch was modeled as three-dimensional and the crack displacement at the edge of the pin hole was found by the finite element method. Stress intensity factor is obtained by DCM (Displacement Correlation Method) which can be applied to three dimensional crack problems for homogeneous orthotropic materials and the results are presented in graphical form. It has been found that for the crack tips at the same distance from the center of the pin hole, larger hole diameters are a more effective parameter on the stress intensity factor than the larger crack length. It has been found that the effect of the patch material variation on the stress intensity factor is increased at large pin diameters.
Keywords: Stress intensity factor; Orthotropic; Repair; Patch